A preparation method and application of Ni-based catalyst enhanced by radio frequency plasma

Through the combination of cold plasma enhanced the soluble gel method and LA auxiliary agent, the Ni/MCM-41 catalyst with high activity and stability is prepared to solve the problem of being easily damaged at high temperatures at high temperatures, and realized the application of industrialized application. Potential applications in.

CN115920948BActive Publication Date: 2025-01-28CHONGQING UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111111015.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-23
Publication Date
2025-01-28
Estimated Expiration
2041-09-23

AI Technical Summary

Technical Problem

Existing Ni-based catalysts are prone to sintering and carbon deposits at high temperatures, resulting in catalyst deactivation and are difficult to widely use in industrial applications.

Method used

Cold and other ions are used to enhance the soluble gel method, introduce the LA assistant, prepare the load-load Ni/MCM-41 catalyst, and improve the activity and stability of the catalyst through the plasma treatment.

Benefits of technology

The catalytic activity and stability of the catalyst were significantly improved. The initial conversion rates of methane and carbon dioxide at 700 ° C reached 81.7 % and 81.0 %, respectively, and only decreased by 0.8 % after a 10 -hour response.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a Ni-based catalyst prepared by radio frequency plasma enhancement, and belongs to the field of greenhouse gases of CO2 and CH4 and environmental catalytic environment. First, the measured Ni(NO3)2·6H2O, La(NO3)2·6H2O (the total mass of the carrier and the active component Ni is 100%, the mass percentage of the active component Ni in the catalyst is 10%, and the mass percentage of La is 3%) and citric acid (C6H8O7·H2O), n(C6H8O7·H2O):n(metal ion)=1:1.5, add an appropriate amount of deionized water to dissolve it, and obtain a transparent solution; after forming a sol in a 60°C constant temperature heating magnetic stirrer, add a measured MCM‑41 molecular sieve carrier, continue stirring for 1h, place it at room temperature for aging for 6 hours, and then place it in a 110°C oven to obtain a catalyst precursor; after radio frequency plasma treatment (power 200W, atmosphere N2, time 2h), La-modified Ni / La / MCM‑41 / Sol / PN catalyst is obtained. The catalytic activity of the catalyst prepared by the method is significantly improved, and the process is simple, easy to operate and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of CO2 reforming methane reaction, and in particular relates to a preparation method and application of a CO2 reforming catalyst. Background Art

[0002] According to statistics, nearly 1 billion tons of carbon dioxide are now released into the atmosphere every month. The gradual increase in the carbon dioxide content in the ambient air has led to a dangerous increase in the temperature of the earth's surface. In this case, converting greenhouse gases into valuable chemicals may help. At present, CO2 is used in the production of fossil fuels and chemical energy products, and has a good application prospect. Carbon dioxide reforming methane can effectively utilize greenhouse gases to generate H2 and CO synthesis gas, which can be further synthesized into other industrial raw materials. While improving the recycling of greenhouse gases, it promotes the production of other industrial raw materials. Therefore, this reaction has received more and more attention in recent years.

[0003] The reaction of CH4 and CO2 will only react at a high temperature of 800℃, so the activation energy of the reaction is very high, and a catalyst is needed to reduce the activation energy of the reaction, and the reaction has many side reactions. The precious metal catalysts (Pd, Pt, Rh, Ru and Ir) that have been studied have good catalytic activity, stability, and anti-carbon deposition performance, but the cost of using precious metals as catalysts is very high, and it is difficult to apply them to industrialization. Ni-based and Co-based catalysts have good catalytic activity and low application cost, but under high temperature reactions, while promoting the conversion of methane to carbon dioxide in the reaction, they also promote the cracking of methane. Therefore, the easy sintering and carbon deposition of Ni-based catalysts leading to catalyst deactivation is the biggest obstacle to the widespread application of Ni-based catalysts. Therefore, it is particularly important to improve the anti-carbon deposition performance and stability of Ni-based catalysts while ensuring the catalytic activity of Ni catalysts.

[0004] Qian et al. used P123 as a template and prepared SBA-15 carrier by hydrothermal synthesis. Different contents of La were added to Ni(NO3)2 aqueous solution to co-impregnate SBA-15. After drying in a water bath, the catalyst precursor was placed in a muffle furnace for calcination to obtain Ni / La / SBA-15 catalyst with high reforming activity and stability. However, the price of surfactant P123 is relatively expensive and the preparation of SBA-15 carrier is more troublesome. Mo et al. prepared Ni / La / Al2O3 catalyst by hydrolysis precipitation method. NH2(CH2)2OH was used as a precipitant. A certain amount of nickel nitrate and an unknown amount of La(NO3)3 were dissolved in a hydrothermal synthesis reactor, and then Al2O3 was added. NH2(CH2)2OH was dripped into the mixture at a rate of 1mL / min. After aging for 2 hours, the reactor was placed in an oven to dry and then cooled to room temperature. The mixture was washed with distilled water in a Buchner funnel until it was neutral to obtain a filter cake, which was placed in an oven for 3 hours and then calcined in a muffle furnace to obtain Ni / La / Al2O3 catalysts with different contents. The obtained catalysts have high activity and stability, but the preparation process is relatively complicated and time-consuming.

[0005] Although the catalysts prepared by the above-mentioned literature methods have obtained good reaction performance of carbon dioxide reforming to produce synthesis gas, there are still problems such as high cost, complicated preparation process, and difficulty in industrialization. Therefore, it is an urgent need for industrial application to study Ni-based reforming catalysts with simple preparation process, low cost and excellent performance. The present invention introduces La auxiliary agent to prepare supported Ni / MCM-41 catalyst in the simple and easy-to-operate plasma enhanced sol-gel method, and studies the effects of plasma treatment time and plasma enhanced different preparation methods on the structure and reforming catalytic activity of Ni-based catalysts supported by MCM-41 carriers, which are rarely reported.

[0006] The design idea of ​​this patent is to prepare a supported Ni-based catalyst with highly dispersed active components. First, the mesoporous molecular sieve MCM-41 with a high specific surface area is used as a carrier to load the active component Ni to improve the dispersion of the catalytic activity and reduce the particle size; in the preparation process, the plasma enhanced treatment catalyst is introduced to further increase the interaction between the catalytic active components and the carrier, enhance the catalyst's adsorption capacity for carbon dioxide, and thus improve the catalytic activity and stability of the catalyst. Based on previous explorations, we optimized the content of active components and additives by impregnation, with a Ni mass fraction of 10% and an additive mass fraction of 3%. On this basis, we modified the catalyst with metal additives reported in the literature that have strong promoting properties. So we explored and investigated metal additives such as Co, Ce, La and Zr, and found that the stability of the catalysts modified with different additives was significantly different, with La being the best, but overall the activity and stability were not too high. We then analyzed that the stability of the catalyst mainly depends on the interaction between the active components and the carrier and the size of the Ni particles. We then further explored the introduction of plasma to modify the catalyst and found that the precursors prepared by different methods had significant differences in stability after plasma modification. We then optimized the coupling of precursor preparation and catalyst plasma-enhanced preparation, and ultimately optimized the best Ni-based reforming catalyst. Summary of the invention

[0007] The object of the present invention is to provide a preparation method and application of a CO2 reforming catalyst. The method has the advantages of simple process, easy operation and low cost. The catalytic activity and stability of the catalyst treated with cold plasma are significantly improved. Compared with the basic Ni / MCM-41 catalyst, the initial conversion rate of methane at 700°C is 81.7% (an increase of 44.8%), and the carbon dioxide conversion rate is 81.00% (an increase of 31.2%). After 10 hours of reaction, the conversion rates of CH4 and CO2 only decreased by 0.8% and 0.8%, respectively. In order to achieve the above purpose, the technical scheme adopted by the present invention is as follows:

[0008] A preparation method and application of a CO2 reforming catalyst comprises the following steps:

[0009] (1) Weigh Ni(NO3)2·6H2O, La(NO3)2·6H2O (the total mass of the carrier and the active component Ni is 100%, the mass percentage of the active component Ni in the catalyst is 10%, and the mass percentage of the additive is 3%), and a gelling agent citric acid (C6H8O7·H2O), n(metal ion):n(C6H8O7·H2O)=1:1.5, add 30 ml of deionized water, stir until completely dissolved, and obtain a transparent solution;

[0010] (2) adding a magnetic stirrer to the mixed slurry obtained in step (1), and rotating and stirring in a constant temperature heated magnetic stirrer until a sol is formed;

[0011] (3) adding a measured amount of MCM-41 molecular sieve carrier to the gel obtained in step (2) to obtain a mixed slurry, and continuing to stir;

[0012] (4) aging the sol obtained in step (3) at room temperature;

[0013] (5) drying the sol obtained in step (4) in an oven to obtain a catalyst precursor;

[0014] (6) The precursor obtained in step (5) was ground into fine powder and then treated with plasma (200 W, N2, 2 h) to obtain a 10% Ni / 3% La / Sol / PN catalyst.

[0015] According to the above scheme, the gelling agent is citric acid (C6H8O7·H2O).

[0016] Preferably, the added amount of the gelling agent is n(metal ion):n(C6H8O7·H2O)=1:1.5.

[0017] According to the above scheme, the carrier is MCM-41 molecular sieve.

[0018] According to the above scheme, the mass percentage of the carrier is 100%, and the mass percentage of the active component Ni is 10%.

[0019] According to the above scheme, the mass percentage of the carrier is 100%, and the mass percentage of the auxiliary agent La is 3%.

[0020] According to the above scheme, the plasma treatment power is 200 W, the atmosphere is nitrogen, and the treatment time is 2 h.

[0021] According to the above scheme, the stirring temperature is 60°C;

[0022] Preferably, the rotary stirring time is 4-5h;

[0023] The continued stirring time is 1h;

[0024] The aging time is 6h;

[0025] The drying time is 11-13h;

[0026] The drying temperature is 100-120°C.

[0027] The present invention has the following advantages:

[0028] 1. The La-doped Ni-based catalyst prepared by the cold plasma enhanced sol-gel method of the present invention is used for CH4 / CO2 reforming reaction. The catalytic activity of the catalyst is significantly improved compared with the Ni-based catalyst prepared by impregnation. At 700°C, the initial conversion rates of methane and carbon dioxide reached 81.7% and 81.0%, respectively, which are significantly improved compared with the conventional 10% Ni / MCM-41 catalyst. The 10h stability evaluation shows that after 10h of reaction, the conversion rate of CH4 only decreased by 0.8%.

[0029] 2. The Ni / La / Sol / PN molecular sieve catalyst was prepared by plasma enhanced sol-gel method, which has simple process, low cost and easy control.

[0030] Figure 1 This is a stability test chart of the catalysts prepared in Examples 1, 2, 3, 4 and 5.

[0031] Figure 2 This is a stability test chart of the catalysts prepared in Examples 1, 2, 6, 7, 8 and 9.

[0032] Figure 3 This is a stability test chart of the catalysts prepared in Examples 2, 6, 10, 11, 12 and 13.

[0033] Figure 4 The XRD spectra of the catalysts prepared in Examples 1, 2 and 13 are shown. DETAILED DESCRIPTION

[0034] The present invention will be further described below through some implementation examples, but the present invention is not limited thereto.

[0035] Example 1 Preparation of Ni / MCM-41 Catalyst

[0036] 0.991g Ni(NO3) 2· 6H2O was stirred and dissolved in 30ml deionized water, 1.80g MCM-41 molecular sieve carrier was added, and after impregnation at room temperature for 45min, the mixed slurry was evaporated to dryness in a water bath at 60℃, dried at 110℃ for 12h, and calcined at 550℃ in air atmosphere for 4h to obtain Ni / MCM-41 catalyst. The catalyst composition of Example 1 is shown in Table 1.

[0037] Catalyst stability evaluation

[0038] The stability evaluation of the catalyst was carried out in a self-made continuous flow fixed bed reactor. The reaction tube was a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature was measured by a thermocouple placed in the middle of the reaction tube and controlled by a program temperature controller. The gas flow was controlled by a mass flow meter with an air velocity of 36000 ml / (g cat ·min), reaction temperature was 700℃, reaction time was 10h, sampling was performed every 30min. The catalytic performance curve of the catalyst at different time points is shown in the figure Figure 1 The conversion rates of CH4 and CO2 at the beginning and after 10 h of reaction are shown in Table 2.

[0039] Embodiments 2 to 5

[0040] Compared with Example 1, only the catalyst additive is different, and the mass percentage of the additive is 3%. The other processes are the same as Example 1 to obtain the finished catalysts. The catalyst compositions of Examples 2 to 5 are shown in Table 1.

[0041] Catalyst stability evaluation

[0042] According to the evaluation method of Example 1, the stability evaluation of the catalyst was carried out in a self-made continuous flow fixed bed reactor. The reaction tube was a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature was measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature was controlled by a program temperature controller. The gas flow rate was controlled by a mass flow meter, and the space velocity was 36000 ml / (g cat ·min), reaction temperature was 700℃, reaction time was 10h, sampling was performed every 30min. The gas chromatograph was used for online detection. The conversion rates of CH4 and CO2 at the beginning and after 10h of reaction are shown in Table 2.

[0043] Embodiments 6 to 9

[0044] Compared with Example 1, the difference is the precursor treatment method, and the other processes are the same as Example 1, which are as follows: 0.991g Ni(NO3) 2· 6H2O and 0.187gLa(NO3) 2· 6H2O was added to deionized water and stirred to dissolve, 1.74g MCM-41 molecular sieve carrier was added, and after impregnation at room temperature for 45min, the mixed slurry was evaporated to dryness in a water bath at 80°C, and then dried in an oven at 110°C overnight to obtain a catalyst precursor, which was treated with plasma (200W, N2, different treatment times) to obtain Ni / La / MCM-41 / PNxh catalysts. The catalyst compositions of Examples 6 to 9 are shown in Table 1.

[0045] Catalyst stability evaluation

[0046] According to the evaluation method of Example 1, the stability evaluation of the catalyst was carried out in a self-made continuous flow fixed bed reactor. The reaction tube was a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature was measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature was controlled by a program temperature controller. The gas flow rate was controlled by a mass flow meter, and the space velocity was 36000 ml / (g cat ·min), reaction temperature was 700℃, reaction time was 10h, sampling was performed every 30min. The gas chromatograph was used for online detection. The conversion rates of CH4 and CO2 at the beginning and after 10h of reaction are shown in Table 2.

[0047] Embodiments 10 to 11

[0048] The difference from Example 1 is that the preparation method of the catalyst and the treatment method of the precursor are different, as follows: weigh 0.991g Ni(NO3) 2· 6H2O and 0.187g La(NO3) 2· 6H2O, add 30ml deionized water to dissolve it, then add 1.74g MCM-41 carrier, put the mixed slurry into a magnetic stirring pot, adjust the pH value to 11 with NH3·H2O at room temperature, put it into a 70℃ magnetic stirring pot for stirring and aging for 2h, then filter and wash, dry it in an oven at 110℃ overnight to obtain a catalyst precursor, and calcine it at 550℃ for 4h in a muffle furnace to obtain a 10% Ni / 3% La / CP / C catalyst, or treat it with plasma (200W, N2, 2h) to obtain a Ni / La / MCM-41 / CP / PN catalyst. The catalyst compositions of Examples 10 and 11 are shown in Table 1.

[0049] Embodiments 12 to 13

[0050] The difference from Example 1 is that the preparation method of the catalyst and the treatment method of the precursor are different, as follows: weigh 0.991g Ni(NO3) 2· 6H2O and 0.187g La(NO3) 2· 6H2O and citric acid (C6H8O7·H2O), n (metal ion): n (C6H8O7·H2O) = 1:1.5 After forming a gel in a 60°C constant temperature heating magnetic stirrer, 1.74g MCM-41 molecular sieve is added and stirred for 1h, taken out and aged at room temperature for 6h, then taken out and placed in a 110°C oven to obtain a catalyst precursor, which is calcined at 550°C for 4h in a muffle furnace to obtain a Ni / La / MCM-41 / Sol / C catalyst, or treated with plasma (200W, N2, 2h) to obtain a Ni / La / MCM-41 / Sol / PN catalyst. The catalyst compositions of Examples 12 to 13 are shown in Table 1.

[0051] Catalyst stability evaluation

[0052] According to the evaluation method of Example 1, the stability evaluation of the catalyst was carried out in a self-made continuous flow fixed bed reactor. The reaction tube was a quartz tube with an inner diameter of 6 mm and a length of 33 cm. The reaction temperature was measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature was controlled by a program temperature controller. The gas flow rate was controlled by a mass flow meter, and the space velocity was 36000 ml / (g cat ·min), reaction temperature was 700℃, reaction time was 10h, sampling was performed every 30min. The gas chromatograph was used for online detection. The conversion rates of CH4 and CO2 at the beginning and after 10h of reaction are shown in Table 2.

[0053] Example Molecular sieve catalyst composition table:

[0054] The specific embodiment molecular sieve catalyst composition is shown in Table 1:

[0055]

[0056]

[0057] According to the evaluation method of Example 1, the catalytic performance curve of the catalyst at 700°C is as follows: Figure 1-3 The initial and final conversion rates of CH4 and CO2 are shown in Table 2.

[0058] The specific catalyst stability evaluation results are shown in Table 2:

[0059]

[0060] XRD characterization

[0061] Figure 4No characteristic diffraction peaks of La-related compounds were found in the catalyst, indicating that La oxides were well dispersed on the catalyst surface. The characteristic diffraction peak at 2θ=22° is amorphous SiO2. Whether it is La-doped or plasma-treated catalyst, it still maintains the characteristic diffraction peak of amorphous SiO2, indicating that the structure of the carrier is not destroyed. Compared with the conventional Ni / MCM-41 catalyst, the characteristic peak intensity of NiO in the Ni / La / MCM-41 catalyst is weakened and the peak width is widened, indicating that La doping can improve the dispersion of NiO on the catalyst surface. Compared with the Ni / La / MCM-41 catalyst, the characteristic peak intensity of NiO in the Ni / La / MCM-41 / Sol / PN catalyst is significantly weakened and the peak width is widened, indicating that the plasma-assisted enhanced sol-gel method can significantly reduce the particle size of NiO and improve the dispersion of NiO on the catalyst surface. This may be because the sol-gel method can promote the uniformity of NiO at the molecular level on the catalyst surface, and after plasma treatment, the dispersion of NiO is further improved and the particle size of NiO is reduced, thereby improving the catalytic activity and stability of the catalyst.

Claims

1. A method for preparing a Ni-based catalyst by radio frequency plasma enhancement, characterized in that: The method comprises the following steps: (1) Weigh Ni(NO3)2·6H2O, La(NO3)2·6H2O, and gelling agent citric acid (C6H8O7·H2O) in a stoichiometric ratio of n(metal ion):n(C6H8O7·H2O)=1:1.5, add 30 ml of deionized water, and stir until they are completely dissolved to obtain a transparent solution; (2) Add a magnetic stirrer to the mixed slurry obtained in step (1), and rotate and stir in a constant temperature heated magnetic stirrer until a sol is formed; (3) adding a measured amount of MCM-41 molecular sieve carrier to the gel obtained in step (2) to obtain a mixed slurry, and continuing to stir, wherein the measured ratio of MCM-41, Ni(NO3)2·6H2O and La(NO3)2·6H2O is: 1.74 g: 0.991 g: 0.187 g; (4) aging the sol obtained in step (3) at room temperature; (5) drying the sol obtained in step (4) in an oven to obtain a catalyst precursor; (6) The precursor obtained in step (5) is ground into fine powder, and after being treated with radio frequency plasma, a 10% Ni / 3% La / Sol / PN catalyst is obtained, in which the total mass of the carrier and the active component Ni is 100%, the mass percentage of the active component Ni in the catalyst is 10%, and the mass percentage of the auxiliary agent is 3%. The radio frequency plasma treatment time is 2 h, the power is 200 W, and the atmosphere is N2.

2. The method for preparing a Ni-based catalyst by radio frequency plasma enhancement according to claim 1, characterized in that: The stirring temperature is 60°C; The rotating stirring time is 4-5h; The continued stirring time is 1h; The aging time is 6h; The drying time is 11-13h; The drying temperature is 100-120°C.

3. Use of a Ni-based catalyst prepared by radio frequency plasma enhancement in methane carbon dioxide reforming according to the method of claim 1 or 2.

Citation Information

Patent Citations

  • Catalyst for producing synthesis gas by reforming natural gas-carbon dioxide for industry

    CN101462058A